Do traditional economic theories of free riding behavior explain spatial clustering of HPV vaccine uptake?. (August 2019) - McKillop, Caitlin N.; Leonard, Tammy; Pruitt, Sandi L.; Tiro, Jasmin A.
Abstract: Rationale: Geographic clusters of low vaccination uptake reduce the population-level efficacy of vaccination programs. However, little is known about the mechanisms that drive geographic patterns in vaccination rates. Traditional economic theory considers vaccination as a classic public good and suggests that free riding— individuals taking advantage of public goods by relying on others' immunization behavior without contributing toward them — is a primary cause of low vaccination rates. However, behavioral economics suggests that free riding does not fully explain observed individual behavior, and the presence of both high and low clusters of vaccination rates suggest that this theory alone does not fully explain geographic patterns of vaccination. Objective: We assessed geographic clustering of HPV vaccination uptake and examined the evidence for or against free riding in HPV vaccination decisions. Methods: We analyzed HPV vaccination decisions of low-income adolescent females (N = 601) residing in urban neighborhoods in Dallas, Texas, USA during 2011–2012. Spatial econometric models were estimated to assess the relationship between neighborhood vaccination rates and individual vaccination decisions. Results: We found a positive and significant relationship between individual HPV vaccination choices and the average neighborhood vaccination rate at the time parents were making vaccine decisions for their adolescent daughters while controlling for neighborhood sorting and other confounders. Conclusion: Individuals were more likely to complete the HPV vaccination series when others in their neighborhood had already completed the series. We do not find evidence for free riding in HPV vaccination decisions. Highlights: Free riding describes individual's ability to benefit from vaccination decisions of others while remaining unvaccinated. The dominant theory explaining free riding is the public goods model developed by economists. We find no empirical support for free riding in HPV vaccination decisions. HPV vaccination decisions are complex and produce both social- and health-related externalities.